1984
DOI: 10.1042/bj2240399
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the inositol phosphates in thrombin-stimulated, washed rabbit platelets in the presence of lithium

Abstract: Experiments with washed rabbit platelets demonstrate that stimulation with a low concentration of thrombin (0.1 unit/ml), that causes maximal aggregation and partial release of amine granule contents, also causes increased accumulation of [3H]inositollabelled inositol trisphosphate (InsP3) in the presence of 20mM-Li+. This concentration of Li+ was found to inhibit the degradation of inositol phosphates by phosphomonoesterases. This result indicates that phosphatidylinositol 4,5-bisphosphate [Ptdlns(4,5)P2] is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…With regard to the functional responses observed in intact platelets after stimulation with thrombin, e.g. platelet shape change, secretion, aggregation or increase in calcium concentration and phosphoinositide metabolism [28], further studies are required to answer the question whether and how the observed adenylate cyclase inhibition is related to these functional changes.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the functional responses observed in intact platelets after stimulation with thrombin, e.g. platelet shape change, secretion, aggregation or increase in calcium concentration and phosphoinositide metabolism [28], further studies are required to answer the question whether and how the observed adenylate cyclase inhibition is related to these functional changes.…”
Section: Discussionmentioning
confidence: 99%
“…ADP, which stimulates platelet aggregation without causing the secretion of platelet dense-granule contents, causes early changes in phosphoinositides; some of these changes may be due to elevation of cytosolic [Ca2+] (Lloyd et al, 1972(Lloyd et al, , 1973aLeung et al, 1983;Vickers et al, 1982Vickers et al, , 1986a. Turnover of PI has been found to be associated with stimulation of platelets by adrenaline (Deykin & Snyder, 1973;Wallace et al, 1982), although the times of incubation were long, making it difficult to link the PI changes with aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, there have been numerous studies describing its hydrolysis by phospholipase C as one of the earliest events following the binding of a variety of agonists to their membrane receptors [1][2][3][4][5][6][7]. This contributes to an increase of intracytoplasmic Ca 2梅 [8,9] and to activation of calmodulin-dependent protein kinase and protein kinase C [10].…”
Section: Introductionmentioning
confidence: 99%